The evolution of the interpretation of the game in historical and cultural tradition - Mojeiko, Marina A. (Journal of the Belarusian State University. Sociology, 2023)
It is shown that the understanding of the phenomenon of the game is one of the essential moments of the cultural tradition, and the very concept of the game was subjected to significant transformations in the course of its deployment. The game is interpreted as a self-sufficient procedurality, and in the course of the evolution of culture (from classics – through non-classics – to post-non-classics), the understanding of this self-sufficiency expands from its interpretation in terms of axiological plane (game has no external goal, and its excitement does not depend on the outcome of the game) to the interpretation ontological plane (game mechanism is applied by post-non-classical philosophy to the unfolding of the processes of the objective world).
Keywords: game; nerve of game; quasi-reality; unpredictability; excitement; play; game of feelings; game of rhythm; language games; writing game; science games; games of truth; games of structure